Originally Posted by

**HallsofIvy** The first equation is x+ y+ az= a and the second equation is 2x- y+ az= a. Subtracting the second equation from the first, -x+ 2y= 0 or x= 2y. Replacing x with 2y in the equations gives 2y+ y+ az= 3y+ az= a, 2x- y+ az= 4y- y+ az or 3y+ az=a again, and 4x+ 3y+ 3z= 8y+ 3y+ 3z= 11y+ 3z= b. If you multiply 3y+ az= a by 11, you get 33y+ 11az= 11a and if you multiply 11y+ 3z= b by 3, you get 33y+ 9z= 3b.

So now you have 33y+ 11az= 11a and 33y+ 9z= 3b. If you subtract the second of those from the first, what do you get?